PENGEMBANGAN SISTEM INFORMASI PRESENSI BERBASIS ANDROID DENGAN TEKNOLOGI PENGENALAN WAJAH DAN GEOLOKASI UNTUK OPTIMALISASI PENGELOLAAN KEHADIRAN KARYAWAN - Rendi Widjaya; Asrul Sani; Rizal Rizal (STMIK Widuri Jakarta, 2024)
This study aims to develop an Android-based attendance information system by integrating facial recognition and geolocation technologies to enhance the accuracy and efficiency of employee attendance management. Facial recognition technology offers advantages in preventing fraud, such as proxy attendance, while geolocation ensures attendance can only be recorded at predefined locations. The research employs the Research and Development (R&D) method, including stages such as needs analysis, system design, application development, testing, and implementation. The results show that facial recognition achieves an average accuracy of 85.75%, with reduced performance under low-light conditions or when employees wear masks. The geolocation feature achieves an accuracy of 91.5% within a 30-meter radius, minimizing attendance from unauthorized locations. Attendance time per employee decreased from 50 seconds (manual) to 25 seconds (digital), improving efficiency by 50%. Employee attendance increased from 85% to 95%, with 100% elimination of proxy attendance cases. This system significantly improves attendance management, providing a more effective, transparent, and accurate process that positively impacts employee productivity and discipline.